Efektivitas Penggunaan E-Learning Moodle Sebagai Media Pembelajaran Terhadap Nilai Siswa di SMK Ma'arif Kota Mungkid - Gunawan Budi Sulistyo (Bianglala Informatika, 2013)
The technology continues to evolve, taking part in education creates effective learning. At this time there has been a paradigm shift in learning caused by the shifting foundation of education (National Education Policy, Psychological, Sociological, and science and technology).The use of e-learning in this case Moodle, is believed to contribute to the effectiveness of teaching and learning, which in turn can improve students' grades. Through the study efevtivitas known whether Moodle E-learning used in the teaching and learning SMK Maarif Kota Mungkid has lasted effective. This study used a method introduced Mc. DeLone, who apply through kuesioner sampling test to obtain the data. The data were processed with the software and Spss Amos. The result shows there are still obstacles that led to the use of E-learning has not been effective. Kata Kunci: Effectiveness, SEM, Amos, E-learning, Moodle